A double masked randomised 4-week, placebo-controlled study in the USA, Thailand and Taiwan to compare the efficacy of oral valganciclovir and topical 2% ganciclovir in the treatment of cytomegalovirus anterior uveitis: study protocol. Issue 12 (19th December 2019) - Takhar, Jaskirat S; Joye, Ashlin S; Somkijrungroj, Thanapong; Laovirojjanakul, Wipada; Lin, Chang-Ping; Lietman, Thomas M; Porco, Travis C; Keenan, Jeremy D; Gebreegziabher, Elisabeth A; Seitzman, Gerami D; Rose-Nussbaumer, Jennifer; Doan, Thuy A; et al.
Abstract : Introduction: Cytomegalovirus (CMV) anterior uveitis is a recognised cause of anterior uveitis in immunocompetent patients and is preventable cause of vision loss. Ocular sequelae include corneal endothelial damage which can cause corneal oedema and failure, as well as glaucoma. Recurrences of inflammation are common and therefore patients are often exposed to long-term therapy. Oral therapy is available in the form of valganciclovir, although with the caveat of systemic side effects such as bone marrow suppression and renal failure necessitating regular interval laboratory monitoring. Recent reports have demonstrated that topical 2% ganciclovir solution may offer promising treatment outcomes in patients with CMV anterior uveitis with superior safety, cost-effectiveness and convenience profiles. An investigation into the relative equipoise of these therapies is warranted for these reasons. Methods and analysis: The Systemic and Topical Control of Cytomegalovirus Anterior uveitis: Treatment Outcomes (STACCATO) trial is designed as a multicentre, block randomised by site, double-masked, placebo-controlled trial comparing the efficacy of oral valganciclovir, 2% topical ganciclovir and placebo in treating PCR-proven CMV anterior uveitis. Participant clinical evaluation will occur at three study time points by a masked study ophthalmologist over a 28-day period to assess resolution of ocular inflammation (secondary outcome). A control group will provide additional information about the possible impact that the infected host's immune response may play in controlling local viral replication. The primary analysis is an analysis of covariance (three arms) correcting for baseline to compare quantitative CMV viral load in the anterior chamber (AC) aqueous fluid before and 7 days after treatment. Ethics and dissemination: The University of California San Francisco Committee on Human Research and the Khon Kaen University Institutional Review Board have given ethical approval. The results of this trial will be presented at local and international meetings and submitted for peer-reviewed journals for publication. Trial registration number: NCT03576898 .